Destination, Seen Unclearly: Relevance of Head-Up Display Information to Driving Is Unrelated to Its Processing. (September 2017) - Sall, Robert J; Wu, Sijing; Spence, Ian; Feng, Jing
Studies have shown that secondary information presented in spatially commingled environments along with primary tasks can adversely affect the performance of that task, as might be the case for information delivered to drivers by a Heads-Up Display (HUD). However, it is unclear how that message's relevance to the task at hand (e.g., driving) might impact either detection of that message, or performance of a primary task. In this study, participants were asked to enumerate cars on a screen in an experiment that sporadically presented them with semantically similar and dissimilar pieces of information in a spatially intermingled environment. The results indicate that when occupying the same spatial proximity as the primary stimuli, all secondary stimuli disrupt primary task performance, regardless of its relevance to the primary task.